Academic Self-Concept on Bully Victims in Early Adolescent - Anne Cintya Afriliani; Aat Sriati; Efri Widianti (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Bullying that occurs in schools have negative impacts on victims rather than perpetrators. Bullying has an influence on the social adjustment of the victims that affects school achievement. In education, academic self-concept has an important role in the achievement of student learning in school and help students respond to bullying behavior. The aim for this study was to identify the academic self-concept on bully victims in early adolescent that consist of academic, social, and self-regard. This research was a quantitative descriptive research. The population in this research were all bully victims from grade 7 and 8, the sample technique used was total sampling with 91 respondents. Data were taken by using academic self-concept instrument from Sriati which consist of 45 statements using likert scale with validity value 0,339-0,761 and reliability 0,952. The academic self-concept analyzed by mean of both total and each dimension. The results were shown by percentage. The results of this study indicated that some respondents i.e. 47 people (51,6%) had positive academic self-concept and about 44 people (48,4%) had negative academic self-concept. In academic dimension, 48 people (52,7%) had positive aspect, social dimension mostly 55 people (60,4%) had positive aspect, and self-regard most of 51 people (56%) had positive aspect. The positive academic self-concept and negative academic self-concept on bully victims in early adolescents were not much different.